The efficacy of macroeconomic policies in resolving financial market disequilibria: A cross‐country analysis. (10th October 2018) - Singh, Gurcharan; Wilson, Albert; Halari, Anwar
Abstract: This study attempts to evaluate the efficacy of macroeconomic policies in resolving financial market disequilibria and to elucidate the influence of the political landscape and global financial integration on the policymaking process. The current investigation examines three macroeconomic policies: (a) government spending, (b) liquidity provision, and (c) central bank interest rates by analysing 21 countries around the globe. The results suggest that government spending is a suboptimal macroeconomic policy for mitigating imbalances in financial markets, as it may have destabilizing effects. Liquidity provision was found to be ineffective in facilitating financial market stability whereas the adjustment of interest rates was found to be a viable tool for mitigating financial market imbalances. Therefore, an appropriate policy framework would comprise the following: prudent government spending, conditional liquidity provision, and a reduction in interest rates following the development of financial market disequilibria. Furthermore, this study found strong evidence against the notion that political orientations influence policy frameworks, which were designed to redress financial market disequilibria. This study also found that global financial integration does not influence the policymaking process.